Analisis Hukum Jaminan di Indonesia dalam Menjaga Stabilitas Ekonomi - Fajar Luthfianingsih; Theresa Yvone Sidabutar; Syafitri Novia Asyari; Marshanda Aurelia Fitri (Mahalini: Journal of Business Law, 2025)
This article analyzes the role of collateral law in maintaining national economic stability when examined based on the role, system, and also related regulations. Collateral law has an important function in providing protection to creditors and ensuring legal certainty regarding debtor obligations. The purpose of this study is to examine the relationship between collateral law and national economic stability and how the two can influence each other. This study uses a qualitative research method using a normative legal approach based on various sources of reading literature with similar themes or objects of study by paying attention to related regulations or laws. Through this study, it can be understood that collateral law is one of the important components in the Indonesian legal system, especially those related to financial transactions and credit provision. This is what makes the role of collateral law in economic stability in Indonesia very important because collateral law functions as a tool to provide protection to creditors and ensure legal certainty in financial transactions. In Indonesia, collateral law has developed through regulations such as Law Number 4 of 1996 concerning Mortgage Rights. With the existence of an effective collateral law, a banking sector will be created that provides a sense of trust to creditors to carry out financing transactions. This is a very important point in maintaining the stability of the financial system and avoiding economic instability that can arise from banking failures.